International consensus statement on allergy and rhinology: Allergic rhinitis – 2023. Issue 4 (6th March 2023) - Wise, Sarah K.; Damask, Cecelia; Roland, Lauren T.; Ebert, Charles; Levy, Joshua M.; Lin, Sandra; Luong, Amber; Rodriguez, Kenneth; Sedaghat, Ahmad R.; Toskala, Elina; Villwock, Jennifer; Abdullah, Baharudin; et al.
Abstract: Background: In the 5 years that have passed since the publication of the 2018 International Consensus Statement on Allergy and Rhinology: Allergic Rhinitis (ICAR‐Allergic Rhinitis 2018), the literature has expanded substantially. The ICAR‐Allergic Rhinitis 2023 update presents 144 individual topics on allergic rhinitis (AR), expanded by over 40 topics from the 2018 document. Originally presented topics from 2018 have also been reviewed and updated. The executive summary highlights key evidence‐based findings and recommendation from the full document. Methods: ICAR‐Allergic Rhinitis 2023 employed established evidence‐based review with recommendation (EBRR) methodology to individually evaluate each topic. Stepwise iterative peer review and consensus was performed for each topic. The final document was then collated and includes the results of this work. Results: ICAR‐Allergic Rhinitis 2023 includes 10 major content areas and 144 individual topics related to AR. For a substantial proportion of topics included, an aggregate grade of evidence is presented, which is determined by collating the levels of evidence for each available study identified in the literature. For topics in which a diagnostic or therapeutic intervention is considered, a recommendation summary is presented, which considers the aggregate grade of evidence, benefit, harm, and cost. Conclusion: The ICAR‐Allergic Rhinitis 2023 update provides a comprehensive evaluation of AR and the currently available evidence. It is this evidence that contributes to our current knowledge base and recommendations for patient evaluation and treatment.